Factors Influencing Moscow University Students’ Level of Trust in the Russian State Mainstream Media News - Freiberg, Phillip Y.; Chotchakornpant, Kasemsarn (Journal of Public Administration and Governance, 2023)
In the modern social sciences, the concept of confidence or trust is considered an essential element of the socio-cultural potential of each given society. Trust in the institutions of the socio-political system is the basis and condition for its effectiveness and is the central element of its [the system] legitimation. Many researchers view trust in the media from the point of view of public confidence in the authorities, which is formed by providing the media with this or that information. Trust is based on a cognitive process that discriminates among persons and institutions that are trustworthy, distrusted, and unknown. Therefore, the concept of trustworthiness is central to understanding and predicting trust levels. In this work, we viewed trust as a manifestation of social capital. At the same time, trust antecedents are trustworthiness and propensity to trust. Proceeding from the resource approach, the credibility (trustworthiness) of the media is a set of ideas and attitudes of the audience: reflecting the public’s expectations that the media will implement some of the practices that allow the audience to increase or maintain their social resources. The goal of this work was to establish a causational relationship between the level of trustworthiness (social capital) of the political power (via its administration and mass media) and the level of trust in its messages by youth as they are transmitted via MSM; while the rise of information through the Internet is rising in Russia and the overall propensity to trust is falling.